Arduino keyless door lock system with keypad and LCD / Muhammad Ali Mohamad - Mohamad, Muhammad Ali (2021)
Living in this modern era, it is undeniable that most of us rely on technology to connect with the ones far from us or even surviving on a daily basis, working from home and to study from home in this pandemic period. Security become the most aspect that we need to concern about. Security is freedom from, or resilience against, potential harm (or other unwanted coercive change) caused by others. Beneficiaries (technically referents) of security may be of persons and social groups, objects and institutions, ecosystems or any other entity or phenomenon vulnerable to unwanted change. Today, there are many people that affected in economical aspect due to the lockdown implemented around the world and people desperate to go on with life. This can lead to insecurity. Therefore, due to the conditions mentioned above, I have come up with a plan to make an Arduino Keyless System with Keypad and LCD. This project aims to enhance the security of the people using it. This project uses a 4X4 keypad to enter the keys and a DC lock to open or close the door. A 16X2 LCD will be used for display. The Proteus software and Arduino UNO controller will be the major parts in making this project a successful one. I also being able to increase my skills in terms or programming using this software. After that, I proposed the ideas to my supervisor, writing a report of my project and constructing the hardware for prototype of the system. The main components of this project are Arduino UNO microcontroller, 4X4 keypad, LCD for display, DC Lock, relay, 9V battery, 10k potentiometer and 220-ohm resistor. In conclusion, I hope this project will turn out well, successful and give benefit to the society out there in future.